Common Peroneal Nerve Grafting to Repair the Tibial Nerve as a Salvage Procedure in the Treatment of Sciatic Nerve Injury with Long-Segment Defects - Lin, Haodong; Chen, Desong; Hou, Chunlin (Journal of Reconstructive Microsurgery Open, 2018)
Background In sciatic nerve neuropathies, when direct nerve repair is impossible due to a large gap, nerve grafting can be performed. However, the diameters of traditional autologous nerve grafts are too small to cover the whole cross-sectional area of the sciatic nerve. The aim of this study is to present the outcome of common peroneal nerve grafting to repair the tibial nerve in eight patients with sciatic nerve injuries, showing long defects of more than 10 cm.Methods Between 2007 and 2013, the common peroneal nerve was used as an autograft to repair the tibial nerve in eight patients with complete high sciatic nerve injury with long defects. There were 6 men and 2 women with an average age of 31 years (range: 17–44 years). Muscle strength was evaluated using the British Medical Research Council scale. The Semmes–Weinstein monofilament test was used for sensory evaluation.Results The follow-up time for patients ranged from 36 to 60 months, with an average of 48.75 months. Tibial nerve motor function was “good” or “very good” (M3–M4) in five out of eight patients (55.6%). Plantar flexion was not adequate in the rest of the patients. Sensory recovery was “good” or “very good” (S2–S3) in six patients and “inadequate” (S4) in two patients.Conclusion In cases where there were extensive gaps in the sciatic nerve, using the common peroneal nerve as an autograft to repair the tibial nerve provides an alternative to traditional nerve graft repair.
Keywords: sciatic nerve; nerve graft; plantar flexion